Test activities in the continuous integration and delivery pipeline. Issue 4 (4th February 2019) - Mårtensson, Torvald; Ståhl, Daniel; Bosch, Jan
Abstract: Based on 25 interviews with participants from four case study companies that develop large‐scale software embedded systems, this paper presents the Test Activity Stakeholders (TAS) model. The TAS model shows how the continuous integration and delivery pipeline can be designed to include test activities that support four stakeholder interests: "Check changes, " "Secure stability, " "Measure progress, " and "Verify compliance." The model is developed to show how each of the stakeholder interests are best supported by unit/component tests or system tests, by automated testing or manual testing and by tests executed in simulated environments or on real hardware. The TAS model may serve as a starting point for companies when evaluating and designing their continuous integration and delivery pipeline. The validation of the TAS model included twelve individuals from three case study companies. The validation showed that the TAS model is actionable and useful in practice, enabling the identification of stakeholders and showing where improvement efforts should be focused in order to support all stakeholder interests in the continuous integration and delivery pipeline. Abstract : The Test Activity Stakeholders (TAS) model shows how the continuous integration and delivery pipeline can be designed to include test activities that support four stakeholder interests: "Check changes, " "Secure stability, " "Measure progress, " and "Verify compliance." The validation of the TAS model showed that the model is actionable and useful in practice, showing where improvement efforts should be focused in order to support all stakeholder interests in the continuous integration and delivery pipeline.